2011
DOI: 10.1016/j.jvs.2011.09.072
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Internal Carotid Artery Occlusion: A Long-Term Follow-Up Study

Abstract: AAAs. There were 28 deaths (6.1%) following elective repair of 459 incidentally detected AAAs (OR, 0.37; 0.24 to 0.68).Comment: The risk of death in a male patient Ͼ65 years operated for an incidentally detected aneurysm is approximately three times more than one operated on for a screened detected AAA. The data do not permit a "drill down" for why patients operated on for screened AAAs have lower operative mortality than those operated on for incidentally detected AAAs. Reasons could include lower ages and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This finding adds to those in previous studies that investigated associations between impaired CVR and increased stroke risk. 4,11,[19][20][21][22][23][24][25][26][27][28][29][30] Nine of 12 studies found a positive association of reduced or exhausted CVR and recurrent risk of future ischemic events or stroke by using a range of vasodilatory stimuli and CVR metrics. The negative findings may be explained by insufficient vasodilatory stimuli because 2 of the studies with negative findings 3,4 used carbogen (typically 5% CO 2 ), whereas Markus and Cullinane 11 showed that exhausted CVR as assessed by hypercapnia transcranial Doppler with 6% or 8% CO 2 independently predicted future stroke and that the prediction was stronger for 8% CO 2 challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding adds to those in previous studies that investigated associations between impaired CVR and increased stroke risk. 4,11,[19][20][21][22][23][24][25][26][27][28][29][30] Nine of 12 studies found a positive association of reduced or exhausted CVR and recurrent risk of future ischemic events or stroke by using a range of vasodilatory stimuli and CVR metrics. The negative findings may be explained by insufficient vasodilatory stimuli because 2 of the studies with negative findings 3,4 used carbogen (typically 5% CO 2 ), whereas Markus and Cullinane 11 showed that exhausted CVR as assessed by hypercapnia transcranial Doppler with 6% or 8% CO 2 independently predicted future stroke and that the prediction was stronger for 8% CO 2 challenges.…”
Section: Discussionmentioning
confidence: 99%
“…1 The rate of subsequent recurrent stroke in carotid artery occlusion (CAO) has been estimated between 2.4% and 7% per year. [2][3][4] This risk persists in the face of platelet inhibitory drugs and anticoagulation. 5 A key factor in predicting recurrent ischemic episodes in CAO is the presence of hemodynamic impairment, whereby patients with an exhausted cerebrovascular reserve (CVR) and therefore impaired autoregulatory capacity are at higher risk of recurrent episodes of ischemia.…”
mentioning
confidence: 99%